Rehabilitación cardíaca en pacientes con dispositivo de asistencia ventricular izquierda. - Ñamo Chapalbay, Yadira Del Pilar (2025)
Introduction: Left ventricular assist devices (LVADs) constitute a treatment possibility in patients with advanced heart failure, impairs millions of people worldwide. These devices provide mechanical support, improving their function. Cardiac rehabilitation in LVAD patients, based on programs that integrate aerobic training, resistance exercise and adjustments in the device pump speed, optimizes functional capacity and quality of life. Objective: To support the information collected on cardiac rehabilitation in patients with ventricular assistance devices in pursuit of optimal recovery. Methodology: The study was documentary and bibliographic, analyzing existing information on cardiac rehabilitation in patients with LVADs. An inductive and descriptive approach was used based on studies published between 2014 and 2025. Twenty-two articles were selected from databases such as PubMed, ResearchGate, and ScienceDirect. Data collection was performed using keywords and Boolean operators. Results: Twenty-two articles were selected using inclusion and exclusion criteria. Of these, 6 indicated improvements in exercise, 5 used scales for improving quality of life, 9 focused on findings regarding the impact of exercise, and 2 presented no significant differences. Conclusion: Cardiac rehabilitation is a secure and successful approach to treating patients with LVADs. It contributes to physical recovery and psychological well-being and represents an advance in the treatment of heart failure.